Pre-excitation due to accessory sinoventricular connexions associated with coronary sinus aneurysms. A report of two cases. Issue 3 (March 1985) - Gerlis, L M; Davies, M J; Boyle, R; Williams, G; Scott, H
Abstract : Ventricular pre-excitation occurred in two cases in which the accessory pathways between the atria and the ventricles were histologically identified as being associated with aneurysmal malformations of the coronary sinus. In one case the connexions were in the posterior wall of the coronary sinus aneurysm and were not related to the atrioventricular annulus; in the other, a connexion was situated in the anterior wall of the aneurysm in close apposition to the annulus and superficially resembled a Kent fibre. These connexions were considered to be of sinus venosus origin and to represent a modification of the muscular sheath that normally surrounds the coronary sinus but does not continue along the coronary veins. One of the posterior wall connecting bundles was composed of abnormally large Purkinje-like fibres; this may have played some role in the manifestation of the pre-excitation by reducing any mismatch impedance.